Srčni spodbujevalniki - kaj, kdaj in kako - Zupan, Anja (Medicinski razgledi, 2005)
The digital world of computer technologies is becoming increasingly important in all fields of science, including medicine. Many new approaches that seemed to be pure fantasy decades ago are now being realised, in both diagnostics andtreatment. One of these incredible advances in modern medicine are implantable pacemakers, which have undergone tremendous development since first implantation in 1958 by Senning in Sweden. A pacemaker is a small computer that is implanted into the human body and from then on tracks every heartbeat, triggering a pulse when the heart fails to make a contraction. Thisis a device which has thoroughly changed the quality and duration of life of people suffering from cardiac rhythm disturbances: such children are now able to grow up and develop normally into adults and many still active adults do not need to give up their sports activities. The following article discusses some basic issues related to implantable`pacemakers, from principlesof their functioning and indications for their implantation to the essentials of treating patients with this device.
Keywords: Aritmija; Cardiac Pacing, Artificial; Elektrode implantirane; Instrumentation; Methods; Srčno vzpodbujanje, umetno; Utilization; srce; heart; kardiologija; Arrhythmia; Electrodes, Implanted; srčne motnje; srčni spodbujevalci